The impact of suction duration on lung collapse during one-lung ventilation - Hang, Lihua; Ju, Jiajun; Li, Yulin; He, Min (Frontiers in Surgery, 2025)
ObjectiveTo investigate the effect of suction duration on lung collapse when using a bronchial blocker (BB) during single-port video-assisted thoracoscopic surgery (VATS) with one-lung ventilation (OLV).MethodsThis study included 112 patients (39 males, 73 females; aged 18–75 years) with ASA physical status I or II undergoing single-port VATS under general anesthesia. Patients were randomized into four groups: control (0 s), 30 s, 60 s, and 90 s suction groups (−30 cmH₂O; n = 28/group). Lung collapse scores (LCS) were recorded immediately after thoracoscope entry (T0) and at 10 min (T10). The expression of nitric oxide synthase 3 (NOS-3) mRNA in lung tissue was analyzed using PCR. Lung injury pathology scores, the wet-to-dry weight ratio (W/D) of lung tissue, intraoperative hypoxemia, perioperative pulmonary complications, and use of disconnection techniques for inadequate collapse were documented.ResultsAt T0, LCS in the 30 s, 60 s, and 90 s groups were significantly higher than in the control group (P < 0.05), with no differences among the suction groups. At T10, LCS in the 60 s and 90 s groups were significantly higher than in the control group (P < 0.05), while no significant differences were observed between the 30 s and control groups. NOS-3 mRNA expression, lung injury pathology scores, and W/D ratios were comparable across groups. No severe hypoxemia or pulmonary complications occurred. Rescue techniques were required in four control group patients and one patient in the 30 s group but not in the 60 s and 90 s groups (P < 0.05).ConclusionSuction at −30 cmH2O for 60 s immediately after pleural incision during one-lung ventilation with a bronchial blocker in single-port VATS significantly improves lung collapse quality without causing lung injury, making it a clinically recommended practice.